2018
DOI: 10.5194/acp-18-8571-2018
|View full text |Cite
|
Sign up to set email alerts
|

High summertime aerosol organic functional group concentrations from marine and seabird sources at Ross Island, Antarctica, during AWARE

Abstract: Abstract. Observations of the organic components of the natural aerosol are scarce in Antarctica, which limits our understanding of natural aerosols and their connection to seasonal and spatial patterns of cloud albedo in the region. From November 2015 to December 2016, the ARM West Antarctic Radiation Experiment (AWARE) measured submicron aerosol properties near McMurdo Station at the southern tip of Ross Island. Submicron organic mass (OM), particle number, and cloud condensation nuclei concentrations were h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 133 publications
(192 reference statements)
5
39
0
Order By: Relevance
“…With the absence of aerosol concentration measurements aloft, and based on the model comparison with the observations, we suggest that the activated N IFN and N A values during the drizzle event should have been on the order of 0.2 L −1 and 20 cm −3 , respectively. These values are within the typical range of McMurdo wintertime N IFN (below −20 °C) and N A from surface‐based reports (Belosi et al, ; Liu et al, ). It is important to note that these number concentrations are rough estimates, because of numerous unexplored degrees of freedom in the model configuration as well as the many uncertainties associated with the comparison of the model results with the observations.…”
Section: Drizzle Event Modelingsupporting
confidence: 83%
See 1 more Smart Citation
“…With the absence of aerosol concentration measurements aloft, and based on the model comparison with the observations, we suggest that the activated N IFN and N A values during the drizzle event should have been on the order of 0.2 L −1 and 20 cm −3 , respectively. These values are within the typical range of McMurdo wintertime N IFN (below −20 °C) and N A from surface‐based reports (Belosi et al, ; Liu et al, ). It is important to note that these number concentrations are rough estimates, because of numerous unexplored degrees of freedom in the model configuration as well as the many uncertainties associated with the comparison of the model results with the observations.…”
Section: Drizzle Event Modelingsupporting
confidence: 83%
“…For simplicity, we specify a monomodal lognormal aerosol particle size distribution with a geometric mean radius of 0.1 μm and geometric SD of 2, approximated from surface measurements during AWARE (Liu et al, 2018). Aerosol activation follows Abdul-Razzak and Ghan (2000), in which the supersaturation is taken as the local minimum during a time step using the semianalytic treatment of Morrison and Grabowski (2008), which neglects activation (cf.…”
Section: Appendix B: Dharma Model Setupmentioning
confidence: 99%
“…However, the accumulation mode (broadly composed of intermediate particle sizes of 50-500 nm) is composed of a complex mixture of both secondary and primary particles. The relative roles of secondary aerosols produced from biogenic sulfur versus primary sea spray aerosols in regulating cloud properties and amounts above the Southern Ocean is still a matter of debate (Meskhidze and Nenes, 2006;Korhonen et al, 2008;Quinn and Bates, 2011;McCoy et al, 2015;Gras and Keywood, 2017;Fossum et al, 2018). First observations of organic carbon (OC) in size-segregated aerosol samples collected at a coastal site in the Weddell Sea (Virkkula et al, 2006) showed that MSA represented only a few percent of the total OC in the sub-micrometre fraction; recent studies demonstrate that sea bird colonies are also important sources of organic compounds locally (Schmale et al, 2013;Liu et al, 2018) as well as seasonal ice microbiota (Dall'Osto et al, 2017b).…”
Section: Origin and Sources Of Antarctic Aerosolmentioning
confidence: 99%
“…Marine primary organic aerosol (POA) is often associated with sea spray, but recent studies indicate that a fine mode (usually < 200 nm) can have a size distribution that is independent from sea salt (externally mixed), whereas supermicrometre marine aerosols are more likely to be internally mixed with sea salt (Gantt and Meskhidze, 2013). McCoy et al (2015) reported observational data indicating a significant spatial correlation between regions of elevated Chl-a and particle number concentrations across the Southern Ocean and showed that modelled organic mass fraction and sulfate explains 53 ± 22 % of the spatial variability in observed particle concentration. Our study cannot apportion any aerosol related to primary organic aerosol, given the lack of chemical measurements carried out during 2015 at Halley Research Station.…”
Section: Primary Antarctic Aerosolmentioning
confidence: 99%
“…In particular, organic particles emitted from seabird colonies contain large amounts of nitrogen with MS spectral fingerprints overlapping with those of nat-ural amino acids. In the paper by Liu et al (2018), Fouriertransform infrared (FTIR) spectroscopy was employed to probe the sources of particulate organic compounds at another coastal Antarctic site, and the results point to a contribution of marine polysaccharides transported in sea-spray aerosols. Finally, detailed organic speciation using offline analytical techniques with high sensitivity and selectivity suggest further contributions from marine proteinaceous material, terrestrial lipids, and secondary organic compounds (Bendle et al, 2007;Barbaro et al, 2015Barbaro et al, , 2017, but it is unclear how much the concentrations of compounds occurring at pg m −3 relate to that of bulk organic matter.…”
mentioning
confidence: 99%